Trends of Populations indicators in developed and developing countries: A Comparative Study (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: The world’s population seems growing, and expected to reach 7.8 billion by mid- 2020, growing from 7 billion in 2010, 6 billion in 1998, and 5 billion in 1986. The average annual growth rate was nearby 1.1% in 2015–2020, which steadily decreased after it peaked at 2.3% in the late 1960.Trends of population indicators between developed and developing countries seems undistinguishable. Therefore, this study aims to identify trends of population’s indicators in developed and developing countries.MATERIALS AND METHODS: Data were obtained from World Development Indicators (WDI).These survey programs are highly comparable as they share similar sampling approaches and questionnaires designed to estimate standard health indicators.RESULTS: The populations of India, Malaysia and Israel was in increasing trends from 2015-2020 whereas Japan was on declining trend from 2015 to2020 however, the populations of Nepal was slightly decreasing from 2015 to 2018 and then it is in increasing trends. Life expectancy rate of Japan was high due to their specific type of Gene quality i.e. DNA 5178 and the ND2-237Met ND genotype which help the Japanese live longer by protecting them against some adult-onset diseases.CONCLUSIONS: The growing population in emerging nations like India and Nepal emphasizes the need for increased focus on gender parity, healthcare, education, and resource allocation, while Japan's declining population raises concerns about the need for pro-natal policies. Developed nations like Malaysia and Israel should prepare for the potential challenges associated with high birth rates, such as increased service demand and environmental concerns.